HUBUNGAN PENGETAHUAN IBU PEKERJA TENTANG PEMBERIAN PENDIDIKAN SEKS DINI PADA ANAK USIA 3-6 TAHUN DENGAN PENERAPANNYA - Arum Dwi Anjani; Devy Lestari Nurul Aulia (Universitas Batam, 2017)
Sexual behavior shown by particularly preschool children in satisfying their curiosity related to sexual exploitation is an indication of the parents, especially mothers in interpreting curiosity shown by children as a sign that the children are ready to be given sex education. The problem is that sex is still considered as a taboo, especially in children ages 3 to 6 years, let alone cases of sexual abuse of children in Indonesia which reach 62%. The purpose of this study was to see if there is any relationship between knowledge of working mothers on the provision of early sex education in children ages 3-6 years with the implementation in TK (Taman Kanakâ€“kanak, Kindergarten) Pembina II, Batam. Data collection using questionnaires, this research was quantitative with cross sectional approach, place of research was in TK Pembina II, Batam. with a purposive sampling technique as many as 34 respondents. Informants in this study were working mothers who have children ages 3 to 6 years. Data analysis using Chi-square. The result was p-value â‰¤ 0.029 0:05 which meant that knowledge of mothers with the implementation of early sex education in children have a relationship. The Suggestion to the community, especially working mothers in Batam, we should further enhance the early sex education for children due to the increasing number of sexual abuse in children.